FACTORS AFFECTING THE DEVELOPMENT OF TOURISM IN SMALL BUSINESS ENTITIES (IN THE CASE OF NAMANGAN REGION) - M.M. Ibrahimova; A.A. Ikramov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
Any economic development begins with opportunities created for its subjects. The first condition for the effective use of natural resources, absolute advantages and factors is a favorable institutional environment. From this point of view, we considered it expedient to get acquainted with the decision that determined the directions of economic reforms in the region and the factors that positively affect the development of tourism in Namangan region. In recent years (2021-2023), the normative document that serves as a road map for the region is the President of the Republic of Uzbekistan "On the Development Strategy of New Uzbekistan for 2022-2026 Ministers of the Republic of Uzbekistan within the framework of Decree No. PF-60 dated January 28, 2022, in order to define the prospects of industry, agriculture and services in the next five years and the "growth points" of each district and city in the territories of Namangan region Decision No. 211 of the Cabinet "On additional measures for comprehensive socio-economic development of the regions of Namangan region in 2022-2026 and further improvement of the living standards of the population", which deals with the issue of tourism development in the region There are several points of direct attention. First of all, the issue of increasing the number of tourists, in particular, increasing the flow of foreign tourists, by establishing new tourism zones and new tourist routes in the region, it is decided to increase the export volume of tourism services to 10 million dollars, and the flow of tourists visiting the region to 1 million people. For this purpose, it is planned to develop a craft development program in Chust district, focusing on the full use of existing potential and opportunities, and to establish a "Craft Center" in Chust district in order to develop tourism potential. In order to create an environment of domestic and international pilgrimage tourism, it is determined to identify the business entity that wants to establish a craft center and to study their needs to provide a comfortable production and business environment.